The Public Participation In Dealing With Covid-19 Through The Use Of “Pedulilindungi” Application (Special Region Of Yogyakarta) - Hendrawan Agung Mulyono; Dyah Mutiarin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
From the end of 2019 up to 2022, Covid-19 has spread in Indonesia. The government also tries to handle; one of which is through the use of application-based information technology, namely PeduliLindungi. This application was launched to help preventing the spread of Covid-19 by sharing the data and information between people. Therefore, this study examines the public participation level in the use of PeduliLindungi application for handling Covid-19 (Yogyakarta Special Region) and finds out the role of PeduliLindungi application in dealing with the spread of Covid-19. The data used were from the primary data through administering the questionnaire and secondary data (including: journals, books, and official government websites). This study used 2 variables and 7 measurement indicators. The first variable focus on the public participation in the use of PeduliLindungi application, which measures 4 indicators, involving the identification of Covid-19 cases in the Special Region of Yogyakarta, the public understanding of the PeduliLindungi application, the ease of using the PeduliLindungi application and the public attitudes in using the PeduliLindungi application. Then, the second variable was about the application of (PeduliLindungi) in handling Covid-19 which focused on 3 indicators, namely the PeduliLindungi application and its features, the uses and benefits of the PeduliLindungi application, and the PeduliLindungi application as the socialization strategy. The results indicated that the public participation in the use of PeduliLindungi application was sufficient since this was related to the mandatory vaccination for the public although its use was still not optimal, but so far this application had been operated sufficiently and produced positive results for the government and the public, so until now Indonesia situation was getting better from covid-19. Moreover, the government should focus on their aims and highlight the point lines, so the people did not feel confused between one policy to another. Keyword: PeduliLindungi application, public participation, covid-19, public policy, artificial intelligence, technology of information